Al-Fahmu al-Lughawiy li Ahadits al-Bid’ah: Dirasah Tahliliyah li Tsalatsah Ahadits Nabawiyah / Linguistic Understanding of Bid'ah Hadiths: An Analytical Study of Three Prophetic Hadiths - Aksa Muhammad Nawawi; Han Han Ulumudin Ismail; Sultan Ahmad Syafe'i; Nun Athirah Syamil (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study starts from the problem of expanding the understanding of the hadiths contained in bid'ah based on the literal reading of some of its words, without taking into account the field of discourse, the semantic context, the deliberative structure, and the rhetorical style. It aims to analyze three hadiths of the Prophet, namely: "Every innovation is misguided", "Whoever introduces to us what is not from it is a response", and "Whoever does an action that is not in accordance with our command is a response", in order to reveal the specific linguistic controls of the concept of the rejection innovation. The study adopted a qualitative approach based on text analysis, benefiting from semantic, deliberative, and rhetorical analysis, with reference to Arabic dictionaries, hadith commentaries, grammar and rhetoric books. The results showed that the word "all" benefits the general public within the scope of the context and is not correct to separate it from the clues contained in the hadiths. It was also found that the phrases "not from him" and "not on us" make non-adherence to the principles of Sharia and disagreement with its approach a criterion for response. The conditional sentence performs a warning and normative function, while the expression of the infinitive in saying "it is a response" reveals the exaggeration of judgment of a work that has no origin. The addition of the study is to build an integrated reading that combines the semantic, deliberative, and rhetorical levels, and it shows that the object of rejection is not absolute renewal, but rather religious events that are contrary to the legal principles.تنطلق هذه الدراسة من مشكلة التوسع في فهم الأحاديث الواردة في البدعة اعتمادًا على القراءة الحرفية لبعض ألفاظها، من غير مراعاة مجال الخطاب والسياق الدلالي والبنية التداولية والأسلوب البلاغي. وتهدف إلى تحليل ثلاثة أحاديث نبوية، هي: «كل بدعة ضلالة»، و«من أحدث في أمرنا هذا ما ليس منه فهو رد»، و«من عمل عملًا ليس عليه أمرنا فهو رد»، للكشف عن الضوابط اللغوية المحددة لمفهوم البدعة المردودة. اعتمدت الدراسة المنهج النوعي القائم على تحليل النص، مستفيدة من التحليل الدلالي والتداولي والبلاغي، مع الرجوع إلى المعاجم العربية وشروح الحديث وكتب النحو والبلاغة. وأظهرت النتائج أن لفظ «كل» يفيد العموم في نطاق المجال الذي يحدده السياق، ولا يصح فصله عن القرائن الواردة في مجموع الأحاديث. كما تبين أن عبارتي «ليس منه» و«ليس عليه أمرنا» تجعلان عدم الانتساب إلى أصول الشريعة وعدم الموافقة لمنهجها معيارًا للرد. وتؤدي الجملة الشرطية وظيفة تحذيرية ومعيارية، في حين يكشف التعبير بالمصدر في قوله «فهو رد» عن المبالغة في الحكم على العمل الذي لا أصل له. وتتمثل إضافة الدراسة في بناء قراءة تكاملية تجمع بين المستويات الدلالية والتداولية والبلاغية، وتبين أن محل الرفض ليس مطلق التجديد، وإنما الإحداث الديني المخالف للأصول الشرعية.